2005
DOI: 10.3758/cabn.5.4.388
|View full text |Cite
|
Sign up to set email alerts
|

Load-dependent modulation of affective picture processing

Abstract: Because of the biological significance of emotional stimuli, their processing is considered largely automatic. In the study reported herein, we tested the alternative hypothesis-namely, that the processing of emotional stimuli requires some level of attention. Our experiments utilized highly negative and arousing visual stimuli comprising mutilated bodies. All experiments employed a single task, which consisted of determining whether two peripheral bars were like oriented or not, thereby eliminating potential … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

26
158
7
12

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(203 citation statements)
references
References 61 publications
26
158
7
12
Order By: Relevance
“…More specifically, performing an attention-demanding task has been found to attenuate the emotional impact of negative stimuli (Erber and Tesser, 1992;Erthal et al, 2005;Glynn et al, 2002;Morrow and Nolen-Hoeksema, 1990;Pessoa et al, 2002;Van Dillen and Koole, 2007;in press). In recent years, the neural effects of task load on processing of emotional stimuli have begun to receive more systematic attention.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…More specifically, performing an attention-demanding task has been found to attenuate the emotional impact of negative stimuli (Erber and Tesser, 1992;Erthal et al, 2005;Glynn et al, 2002;Morrow and Nolen-Hoeksema, 1990;Pessoa et al, 2002;Van Dillen and Koole, 2007;in press). In recent years, the neural effects of task load on processing of emotional stimuli have begun to receive more systematic attention.…”
mentioning
confidence: 99%
“…From this perspective, cognitive load may cause an emotionally relevant stimulus to simply bypass emotional circuits. Given that most prior research relied on demanding distractor tasks that visually competed with emotional information (Erthal et al, 2005;Okon-Singer et al, 2007;Pessoa et al, 2002), cognitive load may have led participants to overlook some of the emotional information.…”
mentioning
confidence: 99%
“…However, this was not an emotional Stroop paradigm and previous work has demonstrated that emotional distracters can cause representational interference ,Erthal et al, 2005Harris & Pashler, 2004;Mitchell et al, 2006,Okon-Singer et al, 2007,Strange et al, 2003. Of course, in many of these studies the emotional distracters have been visual images ,Erthal et al, 2005Mitchell et al, 2006; though see Harris & Pashler, 2004;Strange et al, 2003). It is possible that while the distracters were sufficiently salient to require additional attentional control, they were not sufficiently salient to actually interfere with behavioral performance.…”
Section: Discussionmentioning
confidence: 98%
“…Previous work has shown that emotional stimuli cause greater interference than neutral stimuli Erthal et al, 2005;Harris & Pashler, 2004;Mitchell et al 2006Mitchell et al ,2007Pessoa et al, 2003;Vuilleumier et al, 2001). This is thought to reflect reciprocal connections between the amygdala and temporal and occipital cortex; the amygdala augments the activation of sensory representations of emotional distracters within occipital and temporal cortex LeDoux, 1996;Mitchell et al, 2007;Pessoa et al, 2002;Vuilleumier et al, 2004).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation